Effects Of Improved Agrotechnical Measures On Harmful Harvesting Of Medium-Fiber Cotton Varieties - Boboyeva Nodira Tokhtamishovna; Negmatova Surayyo Teshayevna (Zien Journals, 2021)
The article shows that in the cotton farms of Surkhandarya region in recent years there is an effective method of improved agro-technical measures against handcuffs, which cause great damage to the cotton crop. It has been scientifically proven that cotton yields increase the percentage of damage to the elements.
Keywords: Cotton Shackles; Seedling Thickness; Twig; Entogen